Trunk flexion measurement for the assessment of low back pain - Miljković, Nadica S.; Bijelić, Goran S.; Đorđević, Olivera C.; Konstantinović, Ljubica M.; Zabaleta, Haritz R.; Šekara, Tomislav B. (Vojnotehnički glasnik / Military Technical Courier, 2014)
Low Back Pain (LBP) is one of the most common incidences all over the world. For the assessment of LBP, descriptive medical scores are widely used. Nevertheless, there is a need for the quantitative assessment of LBP by appropriate physiological and kinematic measurements. Quantitative assessment methods are of interest since they might provide reliable and repeatable measures related to low back pain in both everyday clinical practice and at home or work. In this paper, we proposed simple measurements of the trunk angle and the activity of back muscles during simple flexion/relaxation task for an improved assessment of LBP (Low Back Pain). The application of the proposed instrumentation and signal processing is evaluated in three healthy subjects and in two individuals with LBP.The presented data analysis indicates that angle velocity might be a promising parameter in a combination with electromyography profiles for differentiation between healthy subjects and in individuals with LBP for improved medical diagnostics and assessment.